2018
DOI: 10.1186/s13756-018-0315-3
|View full text |Cite|
|
Sign up to set email alerts
|

The knowledge, attitudes and practices of doctors regarding antibiotic resistance at a tertiary care institution in the Caribbean

Abstract: BackgroundAntibiotic resistance (ABR) is a serious threat that requires coordinated global intervention to prevent its spread. There is limited data from the English-speaking Caribbean.MethodsAs part of a national programme to address antibiotic resistance in Jamaica, a survey of the knowledge, attitudes and antibiotic prescribing practices of Jamaican physicians was conducted using a 32-item self-administered questionnaire.ResultsOf the eight hundred physicians targeted, 87% responded. The majority thought th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
(20 reference statements)
2
19
0
1
Order By: Relevance
“…In accordance with the previous studies (Wood et al, 2012;Navarro-San Francisco et al, 2013;Cotta et al, 2014;Sutthiruk et al, 2018), only 36.9% (325/881) HCPs agreed with the statement that "AMR affects patients under their care" even though AMR is increasing day by day (Laxminarayan et al, 2013;Nellums et al, 2018). Furthermore, a handful of pharmacists were in agreement with this statement, as in Pakistan, hospital pharmacists are primarily involved in the provision of traditional services including dispensing of drugs and record-keeping and do not provide many clinical services (Azhar et al, 2009;Azhar et al, 2011).…”
Section: Questionssupporting
confidence: 79%
See 1 more Smart Citation
“…In accordance with the previous studies (Wood et al, 2012;Navarro-San Francisco et al, 2013;Cotta et al, 2014;Sutthiruk et al, 2018), only 36.9% (325/881) HCPs agreed with the statement that "AMR affects patients under their care" even though AMR is increasing day by day (Laxminarayan et al, 2013;Nellums et al, 2018). Furthermore, a handful of pharmacists were in agreement with this statement, as in Pakistan, hospital pharmacists are primarily involved in the provision of traditional services including dispensing of drugs and record-keeping and do not provide many clinical services (Azhar et al, 2009;Azhar et al, 2011).…”
Section: Questionssupporting
confidence: 79%
“…This difference in views towards AMR problem will affect the development of local guidelines to treat resistant infections. Nevertheless, a lot of studies published have also found this inconsistent perception as physicians do not always believe that AMR affects their practice in their practicing hospitals (García et al, 2011;Navarro-San Francisco et al, 2013;Hayat et al, 2019c). This may be because the use of antibiotics without a prescription is common in some countries like Pakistan, China, Saudi Arabia, and Ethiopia and HCPs link the rise in AMR in hospitals to the irrational use of antibiotics in the community outside of the hospital (Abdulhak et al, 2011;García et al, 2011;Chang et al, 2017;Erku and Aberra, 2018;Hayat et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…This frustration results in other-blaming, with both vets and farmers laying the blame for increasing AMR and bad practice on other parties, including other vets and farmers, doctors and patients, and other antimicrobial users across the globe. Vets and farmers are not, however, the only groups to other-blame and locate the issue of AMR elsewhere; surveys of doctors in Ghana and Jamaica have shown they consider AMR to be of greater threat to global or national communities as compared to their local communities or institutions (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…The original article [ 1 ] contains a major error whereby the present title does not display the correct wording as intended by the authors.…”
Section: Correctionmentioning
confidence: 99%